The Red-Blue Conundrum: An Archaeo-linguistic Approach to Red Dyes and Blue Flowers in Prehistory - Nørtoft, Mikkel (Archaeological Textiles Review, 2017)
Plants from the Rubiaceae family (Rubia, Galium, and Asperula) are often grouped together as madder because they have been used for dyeing red since at least the Bronze Age. The English plant name madder can be traced through the Germanic language all the way back to Proto-Indo-European (PIE), as spoken by pastoralists on the Pontic-Caspian steppes c. 4500 to 2500 BC. The word can be reconstructed as PIE *modʰ-r- by the comparative linguistic method. However, there is a difficulty with this. The other Indo-European language branches indicate an original meaning of ‘blue’ for this word, which is hard to reconcile with the appearance and use of Rubiaceae. In the search for the missing link between madder-red and the original PIE meaning of ”blue”, this paper widens the scope of dyeplants to others with pigmented roots. It suggests that the missing link could be a blue-flowered plant species from the Boraginaceae family which has red-pigmented roots, perhaps originally used for cosmetics.